2016
DOI: 10.1159/000452541
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Th17/Treg in Different Subtypes of Autoimmune Thyroid Diseases

Abstract: Aims: To clarify the imbalance of Th17/Treg in different subtypes of autoimmune thyroid diseases (AITDs) including Graves' disease(GD), Hashimoto's thyroiditis(HT) and Graves' ophthalmopathy (GO). Methods: 47 patients with AITD (including 16 GD, 15 HT, and 16 GO) and 12 healthy controls were enrolled in this study. The percentages of Th17 and Treg cells, the ratio of Th17/Treg, as well as their related transcription factors RORγt and Foxp3 mRNA in peripheral blood mononuclear cells (PBMCs) were measured by flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
69
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 27 publications
4
69
0
5
Order By: Relevance
“…The impact of Th17/regulatory T (Treg) immune imbalances (i.e., elevated Th17 response, depressed Treg function) is critical to the pathogenesis of SLE [4][5][6][7], just like other autoimmune diseases [8]. Interleukin (IL)-17A, IL-17F, and IL-22 production by Th17 cells promotes the autoimmune response [9].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of Th17/regulatory T (Treg) immune imbalances (i.e., elevated Th17 response, depressed Treg function) is critical to the pathogenesis of SLE [4][5][6][7], just like other autoimmune diseases [8]. Interleukin (IL)-17A, IL-17F, and IL-22 production by Th17 cells promotes the autoimmune response [9].…”
Section: Introductionmentioning
confidence: 99%
“…Its etiology appears to be the interactions between genetic and environmental factors. GD and HT are characterized by immunocytes’ imbalance and autoantibodies’ production [1]. The HLA-DR3 gene was identified as a susceptible region for AITD [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Treg/Th17 balance plays a key role in maintaining the stability of the immune state [9, 10]. An imbalance can cause a series of immune inflammatory responses that are characteristic of cancer, autoimmune diseases, atherosclerosis, allergic asthma and diseases of the development process [11-15]. Clinical studies have found that the presence of Treg cells in patients undergoing dialysis for end-stage renal failure significantly reduced the frequency of cellular and functional damage and significantly increased the Th17 cell frequency [16].…”
Section: Introductionmentioning
confidence: 99%